Repurposing mucosal delivery devices for live attenuated tuberculosis vaccines - Puri, Munish; Miranda-Hernandez, Socorro; Subbian, Selvakumar; Kupz, Andreas (Frontiers in Immunology, 2023)
Tuberculosis (TB) remains one of the most lethal infectious diseases globally. The only TB vaccine approved by the World Health Organization, Bacille Calmette-Guérin (BCG), protects children against severe and disseminated TB but provides limited protection against pulmonary TB in adults. Although several vaccine candidates have been developed to prevent TB and are undergoing preclinical and clinical testing, BCG remains the gold standard. Currently, BCG is administered as an intradermal injection, particularly in TB endemic countries. However, mounting evidence from experimental animal and human studies indicates that delivering BCG directly into the lungs provides enhanced immune responses and greater protection against TB. Inhalation therapy using handheld delivery devices is used for some diseases and allows the delivery of drugs or vaccines directly into the human respiratory tract. Whether this mode of delivery could also be applicable for live attenuated bacterial vaccines such as BCG or other TB vaccine candidates remains unknown. Here we discuss how two existing inhalation devices, the mucosal atomization device (MAD) syringe, used for influenza vaccine, and the Respimat® Soft Mist™ inhaler, used for chronic obstructive pulmonary disease (COPD) therapy, could be repurposed for mucosal delivery of live attenuated TB vaccines. We also outline the challenges and outstanding research questions that will require further investigations to ensure usefulness of respiratory delivery devices that are cost-effective and accessible to lower- and middle-income TB endemic countries.